Alginate Oligosaccharides Alleviate Salt Stress in Rice Seedlings by Regulating Cell Wall Metabolism to Maintain Cell Wall Structure and Improve Lodging Resistance - Youwei Du; Huimin Zhao; Naijie Feng; Dianfeng Zheng; Aaqil Khan; Hang Zhou; Peng Deng; Yaxing Wang; Xutong Lu; Wenxin Jiang (Plants, 2024)
Salt stress is one of the major abiotic stresses that damage the structure and composition of cell walls. Alginate oligosaccharides (AOS) have been advocated to significantly improve plant stress tolerance. The metabolic mechanism by which AOS induces salt tolerance in rice cell walls remains unclear. Here, we report the impact of AOS foliar application on the cell wall composition of rice seedlings using the salt-tolerant rice variety FL478 and the salt-sensitive variety IR29. Data revealed that salt stress decreased biomass, stem basal width, stem breaking strength, and lodging resistance; however, it increased cell wall thickness. In leaves, exogenous AOS up-regulated the expression level of OSCESA8, increased abscisic acid (ABA) and brassinosteroids (BR) content, and increased β-galacturonic activity, polygalacturonase activity, xylanase activity, laccase activity, biomass, and cellulose content. Moreover, AOS down-regulated the expression levels of OSMYB46 and OSIRX10 and decreased cell wall hemicellulose, pectin, and lignin content to maintain cell wall stability under salt stress. In stems, AOS increased phenylalamine ammonia-lyase and tyrosine ammonia-lyase activities, while decreasing cellulase, laccase, and β-glucanase activities. Furthermore, AOS improved the biomass and stem basal width and also enhanced the cellulose, pectin, and lignin content of the stem, As a result, increased resistance to stem breakage strength and alleviated salt stress-induced damage, thus enhancing the lodging resistance. Under salt stress, AOS regulates phytohormones and modifies cellulose, hemicellulose, lignin, and pectin metabolism to maintain cell wall structure and improve stem resistance to lodging. This study aims to alleviate salt stress damage to rice cell walls, enhance resistance to lodging, and improve salt tolerance in rice by exogenous application of AOS.